Hypothalamic expression of huntingtin causes distinct metabolic changes in Huntington's disease mice - Elna Dickson; Rana Soylu-Kucharz; Åsa Petersén; Maria Björkqvist (Elsevier, 2022)
Objective: In Huntington's disease (HD), the disease-causing huntingtin (HTT) protein is ubiquitously expressed and causes both central and peripheral pathology. In clinical HD, a higher body mass index has been associated with slower disease progression, indicating the role of metabolic changes in disease pathogenesis. Underlying mechanisms of metabolic changes in HD remain poorly understood, but recent studies suggest the involvement of hypothalamic dysfunction. The present study aimed to investigate whether modulation of hypothalamic HTT levels would affect metabolic phenotype and disease features in HD using mouse models. Methods: We used the R6/2 and BACHD mouse models that express different lengths of mutant HTT to develop lean- and obese phenotypes, respectively. We utilized adeno-associated viral vectors to overexpress either mutant or wild-type HTT in the hypothalamus of R6/2, BACHD, and their wild-type littermates. The metabolic phenotype was assessed by body weight measurements over time and body composition analysis using dual-energy x-ray absorptiometry at the endpoint. R6/2 mice were further characterized using behavioral analyses, including rotarod, nesting-, and hindlimb clasping tests during early- and late-time points of disease progression. Finally, gene expression analysis was performed in R6/2 mice and wild-type littermates in order to assess transcriptional changes in the hypothalamus and adipose tissue. Results: Hypothalamic overexpression of mutant HTT induced significant gender-affected body weight gain in all models, including wild-type mice. In R6/2 females, early weight gain shifted to weight loss during the corresponding late stage of disease despite increased fat accumulation. Body weight changes were accompanied by behavioral alterations. During the period of early weight gain, R6/2 mice displayed a comparable locomotor capacity to wild-type mice. When assessing behavior just prior to weight loss onset in R6/2 mice, decreased locomotor performance was observed in R6/2 females with hypothalamic overexpression of mutant HTT. Transcriptional downregulation of beta-3 adrenergic receptor (B3AR), adipose triglyceride lipase (ATGL), and peroxisome proliferator-activated receptor-gamma (PPARγ) in gonadal white adipose tissue was accompanied by distinct alterations in hypothalamic gene expression profiles in R6/2 females after mutant HTT overexpression. No significant effect on metabolic phenotype in R6/2 was seen in response to wild-type HTT overexpression. Conclusions: Taken together, our findings provide further support for the role of HTT in metabolic control via hypothalamic neurocircuits. Understanding the specific central neurocircuits and their peripheral link underlying metabolic imbalance in HD may open up avenues for novel therapeutic interventions.